Design for disassembly: a critical twenty-first century discipline - Bogue, Robert (Assembly automation, 2007)
Purpose - This paper aims to highlight the importance of the design for disassembly (DFD) concept and to consider the key DFD principles.Design methodology approach - This paper first considers the motivations for applying DFD. It then identifies and discusses the key DFD principles.Findings - This paper shows that legislation and consumer pressure are driving product recycling and that DFD is a critical enabling technology. It shows that a series of simple design rules concerning product architecture, materials and fasteners can be used to implement DFD. It highlights the benefits arising from this strategy which include compliance with legislation and reduced component counts and material inventories.Originality value - This paper provides an insight into the motivations behind the use of DFD and describes the techniques used in its implementation.